Millennial Generation (Gen-Y) Preferences Towards Landed House Ownership in Yogyakarta Urban Agglomeration Using Logistic Regression - Prativi, Fatima Putri; Yuniarti, Nur Aini; Kamara, Ibrahin Sorie (Universitas Ahmad Dahlan, Yogyakarta, 2024)
The city of Yogyakarta has become a magnet for the millennial generation (Gen-Y), leading to increased urbanization as residents flock to the city. This surge has resulted in a growing demand for land to accommodate public facilities, social amenities, and housing for workers. Despite soaring land prices, driven by high demand, land stocks have not diminished. Over the last 16 years, land prices have escalated by 30 times. However, the wages of Gen-Y formal workers in the DIY region stand at IDR 2,361,434, with an annual increase of only 8.51%. This rapid growth in property prices has not kept pace with the income growth of the millennial generation, raising concerns about their ability to access landed house ownership. This study aims to identify the preferences of the millennial generation regarding landed house ownership in the Yogyakarta Urban Agglomeration. The analytical method employed is Logistic Regression, involving 125 respondents of Gen-Y workers aged 27 to 41 years in the Yogyakarta Urban Agglomeration. Seven variables, encompassing 25 categorical predictors, were considered. The significant indicators influencing Gen-Y preferences in landed house ownership include the cost of building a house, building materials, and the nominal installment of the house. The findings of this research can be instrumental for relevant stakeholders in formulating policies in the housing sector, particularly in the regulation of subsidized housing for the Gen-Y. The contribution of this study lies in providing essential information for informed decision-making and effective policy implementation to tackle the housing challenges faced by the millennial generation in the Yogyakarta Urban Agglomeration.